2006
DOI: 10.1002/joc.1440
|View full text |Cite
|
Sign up to set email alerts
|

Simulated changes in active/break spells during the Indian summer monsoon due to enhanced CO2 concentrations: assessment from selected coupled atmosphere–ocean global climate models

Abstract: Abstract:The simulations by ten coupled GCMs under the Intergovernmental Panel on Climate Change Assessment Report-4 are used to study the implication of possible global climate change on active/break spells of the Indian summer monsoon (ISM). The validation of the mean daily cycle of the summer monsoon precipitation over the Indian core region and the spatial pattern of the ISM precipitation climatology with observation suggest that six models simulate fairly well, whereas four models differ from observation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…Mandke et al (2007) examined 6 models in the CMIP3 archive using a precipitation index and found inconsistent responses even among the same model to different forcing scenarios. Of particular concern is the ability of coarse resolution GCMs to simulate the finer details of the spatio-temporal evolution of active-break events.…”
Section: Active/break Cycles and Extreme Eventsmentioning
confidence: 99%
“…Mandke et al (2007) examined 6 models in the CMIP3 archive using a precipitation index and found inconsistent responses even among the same model to different forcing scenarios. Of particular concern is the ability of coarse resolution GCMs to simulate the finer details of the spatio-temporal evolution of active-break events.…”
Section: Active/break Cycles and Extreme Eventsmentioning
confidence: 99%
“…Since the study of Ramamurthy (1969), active spells and weak spells/breaks of the Indian summer monsoon have been extensively studied, particularly in the last decade (e.g., Sikka and Gadgil 1980;Magana and Webster 1996;Rodwell 1997;Webster et al 1998;Krishnan et al 2000;Krishnamurthy and Shukla 2000, 2008; Annamalai and Slingo 2001;Goswami and Ajayamohan 2001;Lawrence and Webster 2001;De and Mukhopadhyay 2002;Gadgil and Joseph 2003;Goswami et al 2003;Waliser et al 2003;Kripalani et al 2004;Wang et al 2005;Mandke et al 2007 and the recent reviews by Goswami 2005 andWaliser 2006). However, different scientists have used the same term 'break', to denote different features of convection and/or circulation over different regions.…”
Section: Introductionmentioning
confidence: 99%
“…Annamalai and Slingo (2001) used the daily all-India rainfall based on data at more than 200 stations representing the whole country. Mandke et al (2007) identified the active/break days on the basis of the precipitation anomaly over an area [73][74][75][76][77][78][79][80][81][82] • E, 18-28…”
Section: Introductionmentioning
confidence: 99%
“…Bhaskaran et al (1995) did not notice any significant change in the intraseasonal variability with doubled CO 2 in the UK met office climate model. Changes in the number of active/break spells in rainfall and their duration with climate change in most of the models are small (Mandke et al 2006). However, the reduction in precipitation during the break spells is statistically significant when CO 2 is quadrupled.…”
Section: Intraseasonal Variationmentioning
confidence: 86%
“…They anticipate substantial hazards (landslides, crop damage and flash floods) related to heavy rain events in central India in the future. Most AR4 models show a modest increase in day-to-day variation in summer monsoon rainfall over central India in 2xCO 2 climate, and stronger variation in 4xCO 2 climate (Mandke et al 2006). …”
Section: Intraseasonal Variationmentioning
confidence: 99%